Winger - Smith, Andrew, (Andrew Anselmo), 1959- (New York : Simon & Schuster Books for Young Readers, 2013)
Two years younger than his classmates at a prestigious boarding school, fourteen-year-old Ryan Dean West grapples with living in the dorm for troublemakers, falling for his female best friend who thinks of him as just a kid, and playing wing on the Varsity rugby team with some of his frightening new dorm-mates.
Keywords: Boarding schools -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Rugby football -- Fiction